Legal Counseling Regarding the Limits of Debt Collector and Leasing Authority in the Execution of Motor Vehicles - Lesmana, Sri Jaya; Ristiyana, Rida (PT Agung Media Publisher, 2025)
Unauthorized motor vehicle executions by debt collectors and leasing companies in Indonesia often violate legal provisions, causing public confusion and concerns about consumer rights. According to Constitutional Court Decision No. 18/PUU-XVII/2019, such executions must follow legal mechanisms, like court orders or debtor approvals. This community service activity aimed to enhance public understanding of the legal limits of debt collectors' and leasing companies' authority in bad credit cases. An educational and preventive approach was used, involving discussions, question-and-answer sessions, and simulations to clarify legal processes and consumer rights in vehicle financing. The evaluation showed a significant improvement in participants' understanding, with 91.88% demonstrating enhanced knowledge of the lawful authority of debt collectors, leasing companies, and legal execution mechanisms. These findings highlight the importance of legal education in empowering consumers to protect their rights and ensuring compliance with applicable laws. This program effectively increased public legal awareness and is expected to help reduce unlawful execution practices. Continued efforts in legal education are recommended to sustain and expand these positive outcomes.